2002
DOI: 10.1161/01.cir.0000021599.56755.a1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Assessment of Meloxicam, a Preferential Cyclooxygenase-2 Inhibitor, in Acute Coronary Syndromes Without ST-Segment Elevation

Abstract: Background-Despite the use of heparin, aspirin, and other antiplatelet agents, acute coronary syndrome patients without ST-segment elevation remain at risk of cardiovascular thrombotic events. Given the role of inflammation in the pathogenesis of arterial thrombosis, we tested the hypothesis that the combination of meloxicam, a preferential COX-2 inhibitor, and heparin and aspirin would be superior to heparin and aspirin alone. Methods and Results-In an open-label, randomized, prospective, single-blind pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…IL-1 β immune reactivity is found in monocyte, macrophage, EC, and VSMC in human and experimental atherosclerotic plaque. According to several epidemiological and experimental studies, natural or synthetic products, having anti-inflammatory action, are proven to have a strong preventive effect on the development of atherosclerosis [42]. To investigate the potential anti-inflammatory activity of AND as an antiatherogenic agent, we had evaluated the role of AND on the inflammatory progression of early atherosclerosis in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 β immune reactivity is found in monocyte, macrophage, EC, and VSMC in human and experimental atherosclerotic plaque. According to several epidemiological and experimental studies, natural or synthetic products, having anti-inflammatory action, are proven to have a strong preventive effect on the development of atherosclerosis [42]. To investigate the potential anti-inflammatory activity of AND as an antiatherogenic agent, we had evaluated the role of AND on the inflammatory progression of early atherosclerosis in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The author concludes that, "the current available COX-2 inhibitors might provide a novel form of therapy for plaque stabilization of patients with atherosclerotic disease and prevention of acute ischemic syndromes." 40 In a study by Altman et al, 41 the use of aspirin plus meloxican, a COX-2 inhibitor, for 30 days in patients with ACS without ST-segment elevation was associated with lower rate of recurrent angina, myocardial infarction (MI), or death. An interesting experiment by Saito et al 42 showed better cardiac function in rats that received a selective COX-2 inhibitor after ligation of the left coronary artery in contrast to the control group.…”
mentioning
confidence: 99%
“…However, the evidence consistently shows worse clinical outcome with their use [49]. To refine this therapy, the NUT-2 trial (Non-steroidal anti-inflammatory drugs in Unstable angina Treatment) utilised meloxicam, a cyclo-oxygenase 2 (COX-2) selective inhibitor, which produced significant reductions in mortality and further MI rates after 90 days [50]. Despite this promising early result, a 2006 meta-analysis concluded that selective COX-2 inhibitors are associated with an increased risk of vascular events [51].…”
Section: Myocardial Infarctionmentioning
confidence: 99%